2007
DOI: 10.1016/j.jbiomech.2007.04.024
|View full text |Cite
|
Sign up to set email alerts
|

A surrogate long-bone model with osteoporotic material properties for biomechanical testing of fracture implants

Abstract: In vitro comparative testing of fracture fixation implants is limited by the highly variable material properties of cadaveric bone. Bone surrogate specimens are often employed to avoid this confounding variable. Although validated surrogate models of normal bone exist, no validated bone model simulating weak, osteoporotic bone is available. This study presents an osteoporotic long-bone model designed to match the lower cumulative range of mechanical properties found in large series of cadaveric femora reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…This model consisted of a 27-mmdiameter and 2-mm-thick cortex made of reinforced epoxy and a trabecular core machined from 10 pcf (0.16 g/cm 3 ) solid rigid polyurethane foam (Pacific Research Laboratories). Previous research demonstrated that five structural properties of this bone surrogate (torsional rigidity and strength, bending rigidity and strength, and screw pull-out strength) matched the lower 16% of the cumulative range reported for cadaver femora 25 . Therefore, this osteoporotic bone surrogate reflected the diminished structural properties seen in osteoporotic femora.…”
Section: Specimensmentioning
confidence: 55%
See 1 more Smart Citation
“…This model consisted of a 27-mmdiameter and 2-mm-thick cortex made of reinforced epoxy and a trabecular core machined from 10 pcf (0.16 g/cm 3 ) solid rigid polyurethane foam (Pacific Research Laboratories). Previous research demonstrated that five structural properties of this bone surrogate (torsional rigidity and strength, bending rigidity and strength, and screw pull-out strength) matched the lower 16% of the cumulative range reported for cadaver femora 25 . Therefore, this osteoporotic bone surrogate reflected the diminished structural properties seen in osteoporotic femora.…”
Section: Specimensmentioning
confidence: 55%
“…For the evaluation of implants in weak bone, a validated model of the osteoporotic femoral diaphysis was used 25 . This model consisted of a 27-mmdiameter and 2-mm-thick cortex made of reinforced epoxy and a trabecular core machined from 10 pcf (0.16 g/cm 3 ) solid rigid polyurethane foam (Pacific Research Laboratories).…”
Section: Specimensmentioning
confidence: 99%
“…Subsequently, the constructs were tested to failure in each loading mode under progressive dynamic loading to determine their strength. Finally, failure tests were repeated in a validated model of an osteoporotic femoral diaphysis 45 to determine construct strength in a worst-case scenario of bridge-plate fixation in osteoporotic bone. Each loading mode and construct was tested in five specimens.…”
mentioning
confidence: 99%
“…These factors are the screw thread, screw design, self-tapping/non-self-tapping screws, coating of the screw, unicortical or bicortical insertion 2,5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Various factors affect it. These factors are the bone features, screw diameter, screw type, predrilling and tapping 2 .…”
Section: Introductionmentioning
confidence: 99%